2018
DOI: 10.1073/pnas.1804134115
|View full text |Cite
|
Sign up to set email alerts
|

Size-tagged preferred ends in maternal plasma DNA shed light on the production mechanism and show utility in noninvasive prenatal testing

Abstract: SignificanceCell-free DNA molecules in the plasma of pregnant women exhibit nonrandom fragmentation with preferred end sites. We studied if such preferred end sites might bear any relationship with fragment lengths of plasma DNA. Short and long plasma DNA molecules were associated with different preferred DNA end sites. Analysis of size-tagged preferred ends could be used for measuring fetal DNA fraction and for facilitating fetal trisomy 21 detection. Fetal preferred end sites were generally located in the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 54 publications
3
115
0
3
Order By: Relevance
“…Similarly, in lung cancer, melanoma and colorectal cancer, fragment sizes of cfDNA derived from tumor were short . Recent research reported that higher nucleosome accessibility allowed endonuclease enzymes to cut gDNA within the nucleosome cores, contributing to a preponderance of shorter cfDNA . Further elucidation of the molecular mechanisms behind cfDNA fragmentation is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in lung cancer, melanoma and colorectal cancer, fragment sizes of cfDNA derived from tumor were short . Recent research reported that higher nucleosome accessibility allowed endonuclease enzymes to cut gDNA within the nucleosome cores, contributing to a preponderance of shorter cfDNA . Further elucidation of the molecular mechanisms behind cfDNA fragmentation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Recent research reported that higher nucleosome accessibility allowed endonuclease enzymes to cut gDNA within the nucleosome cores, contributing to a preponderance of shorter cfDNA. 41 Further elucidation of the molecular mechanisms behind cfDNA fragmentation is needed. Second, some mutations could be detected in both cfDNA and gDNA from F I G U R E 6 Positive circulating tumor DNA (ctDNA) and short fragment size of plasma cell-free DNA (cfDNA) were associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides a new pipeline for finding new molecular markers for cancers from cfDNA by combining SALP-seq and machine learning. In recent years, as a good material for cancer liquid biopsy, plasma cfDNA has been widely analyzed by next generation sequencing (NGS) for finding new molecular markers for cancer diagnosis such as fragment size 43,44 , methylation [45][46][47] , and end coordinate 48,49 . However, the size-based plasma DNA diagnostics still faced some limitations that may challenge its wide application 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The emerging knowledge base on the fundamental biology of cfDNA has been called “fragmentomics.” Compared to maternal cfDNA, cfDNA of fetal origin is shorter, differentially methylated, contains a “nucleosome footprint” that reflects a nonrandom fragmentation pattern, and has characteristic end sites that differ from maternal fragments …”
Section: Fragmentomicsmentioning
confidence: 99%
“…Compared to maternal cfDNA, cfDNA of fetal origin is shorter, 8,9 differentially methylated, 10,11 contains a "nucleosome footprint" that reflects a nonrandom fragmentation pattern, 12 and has characteristic end sites that differ from maternal fragments. 13 In 2019, pioneering researchers at the Li Ka Shing Institute of Health Sciences consolidated these understandings of fetal cfDNA in a publication that opens further opportunities for prenatal diagnosis, oncology, and transplant medicine. In this proof-of-principle study, the authors proposed a new method for nucleosome positioning profiling and quantitative determination of the relative contributions of various tissues in plasma DNA by fragmentation pattern analyses.…”
Section: Fragmentomicsmentioning
confidence: 99%